Mapping disordered proteins with single-molecule FRET - Hofmann, Hagen (Henry Stewart Talks, 2019)
Protein folding and folding landscapes, Single-molecule FRET, Protein collapse, Polymer models to describe protein collapse, The dynamics of unfolded and intrinsically disordered proteins, Rouse models, Internal friction